Axonal damage and outcome in subarachnoid haemorrhage. Issue 6 (16th May 2006) - Petzold, A; Keir, G; Kay, A; Kerr, M; Thompson, E J
Abstract : Background: On the basis of preliminary evidence from patients with subarachnoid haemorrhage (SAH), axonal degeneration is thought to be an underestimated pathological feature. Methods: A longitudinal study in 17 patients with aneurysmal SAH. Ventricular CSF was collected daily for up to 14 days. The neurofilament heavy chain SMI35 (NfH SMI35, a biomarker for axonal damage) was quantified using a standard ELISA (upper limit of normal 0.73 ng/ml). The primary outcome measure was the Glasgow Outcome Score (GOS) at 3 months. Results: Of 148 samples from patients with SAH, pathologically high NfH levels in the CSF were found in 78 (52.7%) samples, compared with 20 (5%) of 416 samples from the reference population (p<0.0001). A pathological increase in NfH was observed in all patients with a bad outcome (GOS 1–3) compared with 8% of those with a good outcome (GOS 4–5, p<0.0001). This increase typically became significant 7 days after the haemorrhage (p<0.01). The result was confirmed by analysing the individual mean NfH concentrations in the CSF (3.45 v 0.37 ng/ml, p<0.01), and was reinforced by the inverse correlation of NfH in the CSF with the GOS (r = −0.65, p<0.01). Severity of injury was found to be correlated to NfH SMI35 levels in the CSF (World Federation of Neurological Surgeons, r = 0.63, p<0.01 and Glasgow Coma Score, r = −0.61, p<0.01). Conclusion: Patients with SAH thus have secondary axonal degeneration, which may adversely affect their outcome.